KONSENTRASI MINIMUM SISTEM LAKTOPEROKSIDASE UNTUK MENEKAN PERTUMBUHAN Escherichia coli PADA SUSU SAPI SEGAR - Bagus Fitriansyah; Ahmad Ni’matullah Al-Baarri; Anang Mohamad Legowo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
Fresh milk production in Central Java has increased every year resulting in the requirement of the rapid and good process for fresh milk handling to keep the quality against bacteria. Lactoperoxidase system (LPOS) was well documented as a strategy to extend the shelf life of fresh milk but it hasn’t been known yet for the minimum level of lactoperoxidase (LPO) utilization to activate LPOS in the milk. The purpose of this study was to analyze minimum concentration of LPO and its components by calculating minimum inhibitory concentration (MIC) against Escherichia coli and total bacteria in fresh milk. LPO was obtained from bovine whey and its purity was analyzed using SDS-PAGE. To activate the LPO performance, two substates namely H2O2 and KSCN were used with various concentrations. The MIC was analyzed 3 times using 3M™ Petrifilm™ Aerobic Count Plates. The result showed that 3.11 unit/mL LPO, 0.03 mM subs-trates have been found as MIC of LPOS against bacteria and Escherichia coli in milk. This result might provide benefit to the utilization of minimal LPOS in fresh milk to safe the amount of LPO.